Fishing for data in the Ross Sea - Blight, LK; Ainley, DG; Ackley, SF; Ballard, G; Ballerini, T; Brownell Jnr, MCL; Cheng, CH; Chiantore, M; Costa, D; Coulter, MC; Dayton, P; Devries, AL; et al. (2010)
We are among the scientists objecting to the eco-certification of Ross Sea Antarctic toothfish (Dissostichus mawsoni), as described by E. Stokstad in his News Focus story “Behind the eco-label, a debate over Antarctic toothfish” (24 September, p. 1596). The public perceives a certification by the Marine Stewardship Council (MSC) to mean an environmentally friendly fishery, not one characterized by the “dearth of key data” as indicated in the article.